uCube: control platform for power electronics - Galassini, Alessandro; Lo Calzo, Giovanni; Formentini, Andrea; Gerada, C.; Zanchetta, Pericle; Costabeber, Alessando (2017)
This paper presents a versatile tool for development, control and testing of power electronics converters. In the last decade, many different expensive off-the-shelf tools for rapid prototyping and testing have been developed and commercialised by few market players. Recently, the increasing diffusion of low cost, Do It Yourself targeted development tools gained market shares previously controlled by conventional players. This trend has been driven by the fact that, despite their lower performances, many of these low cost systems are powerful enough to develop simple power electronics systems for learning and teaching purposes. This paper describes a control platform developed within the University of Nottingham, targeting at the market and application segment in between the expensive off-the-shelf control boards and the low cost emerging systems. The platform is based on the Microzed evaluation board, equipped with the Xilinx Zynq System-on-Chip. Its flexibility, features and performances will be addressed and examples of how they are being experimentally validated on different rigs will be provided.